Financial inclusion by Zimbabwean commercial banks in a liquidity constrained environment - Chikoko, Laurine; Mangwendeza, Patrick (Academic Journals, 2016)
The study investigates the trends and challenges of financial inclusion by commercial banks in Zimbabwe after the adoption of the multiple currency regime. Results showed that some commercial banks made efforts to ensure financial inclusion. New innovations like cell phone banking and internet banking were positive steps towards ensuring financial inclusion by Zimbabwean commercial banks. The foreign owned commercial banks in Zimbabwe however were not doing much as compared to the locally owned commercial banks. A number of challenges to financial inclusion were identified, chiefly being the liquidity challenges and high bank charges. Based on the research findings, we recommend the structuring of sustainable financial products and establishment of supportive infrastructure to enable Zimbabwean commercial banks to mitigate the challenges of financial inclusion in a liquidity constrained environment.